Analisis Pengetahuan, Motivasi Dan Tindakan Masyarakat Dalam Pencegahan Demam Berdarah Dengue - Putra Apriadi Siregar; Yulia Khairina Ashar (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
North Sumatra Province is one of the provinces that has the highest incidence of dengue fever in Indonesia, Binjai City has dengue incidence and even death cases in North Sumatra Province. Community knowledge and motivation are essential to support dengue prevention measures in Binjai City. The purpose of this study was to analyze the relationship between knowledge and motivation on community action in the prevention of dengue fever in Cengkeh Turi Village, Binjai Utara District, Binjai City. This study used a cross-sectional design. The sample in this study was 66 people. Data analysis used the Chi-square test and Prevalent Rate (PR). The results of this study indicate that the chi-square analysis shows that there is a relationship between knowledge (p <0.001) and motivation (p <0.001) with dengue prevention measures (p <0.001) in Cengkeh Turi Village. People who have high motivation have a risk of taking preventive measures for DHF by 5,750 times compared to people who have low motivation. Puskesmas officers in Cengkeh Turi Village, Binjai Utara District expected to make an effort to approach local community groups such as recitation groups and youth groups in increasing community motivation in taking dengue prevention measures.